Changing spatial interconnectivity during the "Great American Migration Slowdown": A decomposition of intercounty migration rates, 1990–2010. Issue 1 (27th October 2019) - DeWaard, Jack; Fussell, Elizabeth; Curtis, Katherine J.; Ha, Jasmine Trang
Abstract: Prior research on the "Great American Migration Slowdown, " or the declining rate of U.S. internal migration in recent decades, is dominated by two research foci. The first is concerned with the determinants of the migration slowdown. The second is concerned with spatial heterogeneity in the migration slowdown in and across places. With respect to the aim of this paper, many studies of spatial heterogeneity in the migration slowdown have implicitly raised questions about whether and to what extent places are connected to one another by migration flows, or the spatial interconnectivity of migration. The spatial interconnectivity of migration is a concrete manifestation of underlying spatial interdependence among places and, as such, deserves to be explicitly unpacked to further our understanding of the migration slowdown. Using county‐to‐county migration flow data from the Internal Revenue Service and a novel application of Das Gupta's demographic standardisation and decomposition procedures, we document changes in the spatial interconnectivity of migration during the migration slowdown between 1990 and 2010. We show that counties became more connected to one another by migration over time and that the increasing spatial interconnectivity of migration helped to keep the migration slowdown from slowing further. We also document changes in the spatial interconnectivity of migration for four types of migration flows: metro‐to‐metro, nonmetro‐to‐metro, metro‐to‐nonmetro, and nonmetro‐to‐nonmetro. Our work further elucidates the characteristics of the migration slowdown by describing changes in the spatial interconnectivity of migration. It also raises new questions for future research about the determinants and consequences of these changes.